Strategies for Improving Service Quality at Tangguwisia Regional Hospital, Buleleng - Purnamawati, Indah (Dinasti Publisher, 2026)
This study aims to analyze the quality of healthcare services and quality improvement strategies at Tangguwisia Regional Hospital (RSUD Tangguwisia), Buleleng, Bali. The method used was descriptive qualitative, using interviews, observation, documentation, and triangulation to test data validity. The results show that RSUD Tangguwisia has achieved full accreditation, reflecting high quality standards through adherence to hand hygiene protocols, efficient triage times, and efforts to prevent patient safety incidents. However, major challenges include limited human resources, particularly specialist doctors, and the need to improve the competency of both medical and non-medical personnel. Strategies implemented include routine training, the use of information technology such as digital registration and electronic medical records, updated standard operating procedures (SOPs), improved facilities and infrastructure, and patient feedback mechanisms. Focusing on the dimensions of reliability, empathy, and responsiveness has been shown to increase patient satisfaction. In conclusion, RSUD Tangguwisia demonstrates a strong commitment to providing quality healthcare services sustainably, although it still requires strengthening in human resources and other quality dimensions.